Student Learning Motivation Factors for the Learning Process in the Classroom at Putra Harapan Junior and Senior High School, Al-Fitroh Islamic Foundation - Rustomo Tomo; Aprillia Nurbaeti; Islah Gusmian; Giyoto Giyoto (Jurnal Ilmiah Iqra', 2024)
Learning is an aid provided by educators so that there can be a process of acquiring knowledge and knowledge, mastering skills and habits and forming attitudes and beliefs in students. This requires an encouragement or motivation for student learning in class in the learning process presented by the school and the teacher's guidance. This is the purpose of the study are the factors that influence student learning motivation towards the learning process in the classroom. With quantitative methods, it is a survey study on seventh grade students of Putra Harapan Junior High School and tenth grade of Putra Harapan High School as samples in this study. Data collection by distributing questionnaires with a linert scale with four statements.Data processing explains the relationship and influence of student learning motivation factors on the learning process. With the results of all data declared valid and reliable, and the relationship is partially low but in simultaneous tests has a moderate contribution.Factors in student learning motivation partially state negative or opposite influences resulting in a decrease in the learning process, but simultaneously state positively and significantly.